Penerapan Strategi dan Efektivitas Pendidikan Karakter Anti Korupsi pada Siswa Siswi Ma Ma’arif Cepogo: Penelitian - Fanka Aulia; Bandung Madu Seno; Beny Azzaydan Noval; Bagus Dwi Efendi; Unna Ria Safitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Corruption is a crucial issue that can threaten the values ​​of honesty and morality in society. Therefore, efforts to prevent corruption are needed by instilling it from an early age through educational programs. Socialization in schools by strengthening anti-corruption education is an appropriate strategy by instilling the value of responsibility in shoping the character of the younger generation at MA MAARUF, building students' commitment to strongly rejecting all forms of corruption and implementing it in their daily lives. The methods used include socialization, providing materials, discussions with students, and conducting question-and-answer quizzes. Based on activity studies, instilling morals and the importance of anti-corruption has proven effective in developing an understanding of anti-corruption.